Game Edukasi Pembelajaran Bahasa Inggris untuk Pengenalan Benda-Benda di Rumah bagi Siswa Kelas 4 Sekolah Dasar - Al Irsyadi, Fatah Yasin; Annas, Rifai; Kurniawan, Yogiek Indra (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2019)
English has become one of the international languages ​​in this era. In the world of education, English lessons have been given since elementary school.